Parametric study of gravure printing process for R2R printed electronics - Pua, Suan Tai (2017)
Gravure printing is known to be cost competitive in manufacturing electronics due to its capability to mass produce at lower costs. Current gravure printing standards are in a range of around 50μm to sub-10μm, predominantly through small scale setups and specialised etching. In this study, however, various printing parameters were investigated to establish their effects on printed line width and film thickness, in an attempt to achieve fine line printing resolution over a large printing area. Through a mixed level 2k Design of Experiment (DOE), the effects of the printing parameters- printing speed, ink viscosity, printing angles- were thoroughly investigated. Through the optimisation such printing parameters, it was possible to reduce the printed line width and film thickness over a huge length, with a width of 300mm. New methods of quantifying the ink transfer were also developed to characterise the printed line width more accurately. A model based on adhesion energy and work done was developed in tandem with the empirical results from the DOEs to analyse gravure ink transfer process. In addition to the parametric study, thixotropic behaviours of a composite ink through addition of silver nanostructures were also investigated. It was observed that the shear recovery capabilities of the ink improved through the addition of silver nanostructures. It was postulated that the printed line width could be further reduced through the addition of silver nanostructures and this would be verified in future experiments.